1967
DOI: 10.1177/004051756703701105
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Ester Cross Links into Cotton Cellulose by a Rapid Curing Process

Abstract: The reaction of polycarboxylic acids with cotton at elevated temperature has been investigated as a function of partial neutralization of the carboxylic acid with sodium carbonate or triethylamine. A high level of cellulose cross-linking was realized with a variety of polycarboxylic acids having three or more carboxyl groups per molecule, although only partial esterihcation of the carboxyl groups occurs in this process. The use of polycarhoxylic acids in the form of their partial salts results in broader appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 4 publications
0
33
0
1
Order By: Relevance
“…BTCA has four carboxylic acid groups, which can react with hydroxyl groups of cellulose and form stable ester bonds Morris, Catalano, & Andrews, 1995). Rowland et al (Rowland, 1968;Rowland, Welch, Brannan, & Gallagher, 1967) studied in detail the esterification reactions of PCA with cotton cellulose and the indication was that high levels of cellulose crosslinking could be obtained with PCA with three or more carboxyl groups per molecule. Esterification can occur with heat alone or can be accelerated by the presence of salts of weak acids, such as sodium hypophosphite (SHPI).…”
Section: Introductionmentioning
confidence: 99%
“…BTCA has four carboxylic acid groups, which can react with hydroxyl groups of cellulose and form stable ester bonds Morris, Catalano, & Andrews, 1995). Rowland et al (Rowland, 1968;Rowland, Welch, Brannan, & Gallagher, 1967) studied in detail the esterification reactions of PCA with cotton cellulose and the indication was that high levels of cellulose crosslinking could be obtained with PCA with three or more carboxyl groups per molecule. Esterification can occur with heat alone or can be accelerated by the presence of salts of weak acids, such as sodium hypophosphite (SHPI).…”
Section: Introductionmentioning
confidence: 99%
“…More homogeneous distribution of crosslinks in cotton fibers is beneficial to the wrinkle resistance of the crosslinked cotton fabric. 27 One also observes in Figure 2 that the slope (WRA vs acid concentration) decreased as the acid concentration was raised above the 6% concentration level, probably due to the lack of cellulosic hydroxyl groups to esterify the acid at the high acid levels.…”
Section: Resultsmentioning
confidence: 72%
“…Among the new crosslinking agents being investigated polycarboxylic acids appear to be the most promising agents (Welch, 1992;Welch 1994). Rowland et al (1967) were the first to provide evidence that carboxylic acids could impart crease recovery to cotton coupled with strength retention. In addition, Welch (1988) demonstrated that 1,2,3,4-butanetetracarboxylic acid (BTCA) was the most effective crosslinking agent for cotton cellulose, imparting high crease recovery values and durability to laundering.…”
Section: Crease-resistant Finishing Of Soybean With Polycarboxylic Acidsmentioning
confidence: 99%